TRAVELING WITH MATHEMATICS PROJECT - Bastos, Fernando de Souza (2014)
In order to stimulate and promote the study of mathematics and to collaborate to science knowledge, the extension project "Traveling with mathematics" was developed and had as its main objective to present lectures to High-School students in the city of Florestal - MG and in its region, and by means of these, released details of the undergraduate course in mathematics, of the possibilities of scholarships for students in teaching, research and extension programs, about the labor market for the mathematics professional, named the areas of work and post-graduate opportunities. In the same project, the Federal University of Viçosa – Campus UFV – Florestal and especially the course in Mathematics was presented. Also, a questionnaire was applied in order to analyze the profile of students attending the lecture, potential future students for the Campus UFV – Florestal. The project was developed on an elaborate schedule of visits to schools in the region from April to October, 2011. The original schedule was set to visit two schools a month, except the month of July, month of school holidays. Twelve public schools were visited in the cities of Florestal, Tavares, Itaúna, Para de Minas, Cláudio and Mateus Leme, where about 600 students, in the third year of High School, attended the lecture and 234 of them answered and returned the questionnaire. The questionnaire contained about 30 questions that dealt with social, economic and cultural needs of students, and questions aimed to evaluate the project. The results were very positive, apart from visibility to the campus of Florestal, to the mathematics course offered and the profession in mathematics, the students could see that the University offers help through housing support, food and various kinds of scholarships that they can receive. This motivated students who never even taught of taking a further education.